Étude et conception d’un bâtiment (R+6) à contreventement mixte. - CHERIFA DIFI; SILIA DJOUAMAA (My University, 2023)
The aim of this study is the conception of a for dwelling and commercial of R+6 stages which will be established in the wilaya of Tarf, classified in zone IIaaccording to the Algerian payment parasismic (RPA 99 version 2003). The stability of the work is ensured by the beams, and the columns and the walls. The study and the analysis of this plan had been established by software (ROPOT2000). The calculation of dimensions and the reinforcement of all the resistant elements are in conformity with the rules applicable in strengths to knowing (BAEL91 modifier99, RPA99 -Version 2003). ------------------------------------------------------------------------------------ يهدفهذا المشروع إلى دراسة بناية ذات طابع سكني تتألف من طابق ارضي + 6 طوابق،يتم انجازها بولاية الطارف المصنفة ضمن المنطقة الزلزالية رقم IIaحسب القواعد الجزائرية المضادة للزلازل (RPA99 version 2003). مقاومة واستقرار البناية لكل الحمولات العمودية والأفقية مضمونة بواسطة العارضات، الأعمدةوالجدران المشكلة من مادة الخرسانة المسلحة. الدراسة الحركية تتم بالاستعمال برنامج الي (روبوت). تحديد الأبعاد والتسليح كل العناصر المقاومة للبناية صمم طبق المعايير والقوانين المعمول بها في الجزائر modifier99)(RPA 99 version 2003, BAEL 91 ----------------------------------------------------------------------------------- Le but de cette étude et la conception d'une structure à usage d'habitation de R+6 étages qui sera implanté dans la wilaya d’El Tarf, classé en zone IIa selon le règlement parasismique Algérien (RPA 99 version 2003). La stabilité de l'ouvrage est assurée par les poutres, et les poteaux et les voiles. L'étude et l'analyse de ce projet ont été établies par le logiciel (ROBOT). Le calcul des dimensions et du ferraillage de tous les éléments résistants sont conformes aux règles applicables en vigueurs à savoir (BAEL91 modifier99, RPA99 version 2003).